Visitor segmentation of heritage tourist attraction in Indonesia using google trend analysis - I Gusti Bagus Rai Utama; Ni Putu Dyah Krismawintari; I Wayan Ruspendi Junaedi; PA Andiena Nindya Putri; I Made Sumartana (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2023)
This study aims to determine the popularity of heritage tourist attractions, namely Borobudur, Prambanan, Besakih, and Tanah Lot using the Google Trends tool based on a historical database of the last five years. In addition to popularity, this study also determines the market segmentation of each tourist attraction based on the geographical origin of the tourists. The information and findings are expected to be used as consideration for the destination marketing strategy, and also to determine the promotion on the geographical origin of tourists. This analysis using Google trends yields several conclusions, in the beginning of 2000 to the end of 2021, almost all heritage tourist attractions have decreased in popularity, this is most likely due to a travel ban for tourists during the Covid-19 pandemic. Borobudur Template Heritage Tourism Attraction is the most popular heritage tourist attraction since the last five years, then Prambanan Temple, Tanah Lot, and Besakih. The segmentation of heritage tourism attractions in Indonesia is domestic tourists, and International tourists by Singaporean, Malaysian, Thai, Philippines, South African, Australian, Indian, Taiwanese, Italian, and French. The government should immediately open up opportunities for opening tourism, and tourist attraction managers will intensify the use of information technology, especially digital marketing to display the image of heritage destinations that are open space destinations. is a safe tourist attraction to visit.